Students' perceptions on online learning - Loi, Chek Kim; Lau, Yoke Lian; Soon, Chiow Thai; Ku, Chen Jung (Global Academic Excellence, 2022)
The purpose of this paper is to explore students’ views of online learning based on a theoretical framework known as Technology Acceptance Model (TAM). It is mainly qualitative in nature alongside some quantitative data. It examines students’ preference for their choice of learning mode for the post-COVID-19 period or when they are in a position to return to the campus when the pandemic situation improves. They are also asked to provide reasons for their preference. The research data was collected at a local university in Malaysia through an interview with 41 respondents. The results of the research show that the majority of the student respondents prefer to have hybrid learning that offers a combination of online and face-to-face sessions followed by fully face-to-face learning mode. No respondent has opted for fully online learning as their preferred choice of learning mode in the near future. In general, the respondents perceive that online learning is creative, innovative, convenient, time-saving and eco-friendly. However, as emerged in the data, in relation to online learning, students have two major concerns, namely additional cost incurred for the high usage of the Internet data and poor/no Internet connection at rural areas. The findings further reveal that institutional support, technology accessibility and COVID-19 concern are the three external factors that have influenced the respondents’ attitude and intention in using online learning in the near future. Higher institutions thus can play an important role in enhancing students’ online learning by upgrading the existing learning management system and the campus Internet connectivity.